Anti-malarial drug quality in Lagos and Accra - a comparison of various quality assessments - Bate Roger; Hess Kimberly (Malaria Journal, 2010)
Abstract Background Two major cities in West Africa, Accra, the capital of Ghana, and Lagos, the largest city of Nigeria, have significant problems with substandard pharmaceuticals. Both have actively combated the problem in recent years, particularly by screening products on the market using the Global Pharma Health Fund e.V. Minilab® protocol. Random sampling of medicines from the two cities at least twice over the past 30 months allows a tentative assessment of whether improvements in drug quality have occurred. Since intelligence provided by investigators indicates that some counterfeit producers may be adapting products to pass Minilab tests, the results are compared with those from a Raman spectrometer and discrepancies are discussed. Methods Between mid-2007 and early-2010, samples of anti-malarial drugs were bought covertly from pharmacies in Lagos on three different occasions (October 2007, December 2008, February 2010), and from pharmacies in Accra on two different occasions (October 2007, February 2010). All samples were tested using the Minilab® protocol, which includes disintegration and active ingredient assays as well as visual inspection, and most samples were also tested by Raman spectrometry. Results In Lagos, the failure rate in the 2010 sampling fell to 29% of the 2007 finding using the Minilab® protocol, 53% using Raman spectrometry, and 46% using visual inspection. In Accra, the failure rate in the 2010 sampling fell to 54% of the 2007 finding using the Minilab® protocol, 72% using Raman spectrometry, and 90% using visual inspection. Conclusions The evidence presented shows that drug quality is probably improving in both cities, especially Lagos, since major reductions of failure rates over time occur with all means of assessment. Many more samples failed when examined by Raman spectrometry than by Minilab® protocol. The discrepancy is most likely caused by the two techniques measuring different aspects of the medication and hence the discrepancy may be the natural variation in these techniques. But other explanations are possible and are discussed.